Construction of steel shed: a case study of automobile service center, bells university of technology, Sango-Ota, Ogun state, Nigeria - O. Ajala, M. (International Journal of Physical Research, 2021)
The construction of steel shed for Automobile Service Centre at the Bells University, Sango-Ota, Ogun State, Southwestern Nigeria was deemed necessary in order to expand the existing structure, ensure safety and bring economic gains to the Institution. This paper therefore presents a report of the construction of steel shed at the Automobile Service Centre where activities such as automobile checks, repairs and so on are been carried out. In carrying out the project, the following methods were adopted: evaluation of design/working drawings, selection and fabrication of structural members, construction work and finishing. All methods follow standard procedures as specified in relevant British standards. The assemblage and completed work were the results of the methods mentioned above and it was confirmed that the members were adequate to carry the live and dead loads that they may be subjected to. The aim of the project was achieved.Â Â